Hypogonadism: a neglected comorbidity in young and middle-aged HIV-positive men on effective combination antiretroviral therapy. (1st July 2022) - Lachâtre, Marie; Pasquet, Armelle; Ajana, Faïza; Soudan, Benoit; Quertainmont, Yann; Lion, Georges; Durand, Emmanuel; Bocket, Laurence; Mole, Martine; Cornavin, Pauline; Catalan, Pilartxo; Senneville, Éric; et al.
Abstract : Objective: Male hypogonadism is poorly characterized in young-to-middle-aged people with HIV (PWH). We used a reliable free testosterone assay to assess the prevalence and predictive factors for male hypogonadism in PWH on effective combined antiretroviral therapy (cART). Design: A French cross-sectional study from January 2013 to June 2016. Methods: We included HIV-1-infected men aged between 18 and 50years with HIV loads of 50 RNA copies/ml or less, on effective cART for at least 6 months. Hypogonadism was defined, according to guidelines, as a mean calculated serum free testosterone concentration less than 70pg/ml (Vermeulen equation). Sociodemographic, anthropo-metric, bone-densitometry, hormonal, immunovirological, metabolic, and therapeutic parameters were collected. The IIEF-5, HAM-D, and AMS scales, respectively, assessed erectile function, depression, and quality of life. Results: Overall, 240 patients were enrolled, 231 were analyzed. Low free testosterone concentrations (<70pg/ml) were recorded in 20 patients (8.7%), and were exclusively of secondary origin. In multivariable analysis, the risk factors predictive of male hypogonadism were age more than 43 years [adjusted odds ratio (aOR) 3.17, 95% confidence interval (95% CI) 1.02–9.86; P = 0.04], total fat percentage more than 19% (aOR3.5, 95% CI 1.18–10.37; P = 0.02), and treatment including efavirenz (aOR3.77, 95% CI 1.29–10.98; P = 0.02). A nadir CD4+ T-cell count more than 200 cells/ μl (aOR 0.22, 95% CI 0.07–0.65;P < 0.01) were protective. Conclusion: Male hypogonadism remains common in young-to-middle-aged PWH with stably suppressed viral replication. Treatment including efavirenz, being over 43 years old, and having a total body fat percentage greater than 19% could be used as criteria for identifying PWH at risk. Early screening for male hypogonadism might improve care by identifying patients requiring testosterone replacement.